INNOVATIVE APPROACHES TO ORGANIZING QUALIFICATION AND PEDAGOGICAL PRACTICES OF TECHNOLOGICAL EDUCATION STUDENTS (Multidisciplinary Journal of Science and Technology, 2025)
This article explores innovative approaches to organizing qualification and pedagogical practices of students in the field of technological education. The study emphasizes the importance of integrating modern pedagogical methods, digital technologies, and creative teaching strategies in order to enhance the professional readiness of future teachers. Special attention is given to the development of practical competencies, critical thinking, and problem-solving skills through practice-based learning. The article also highlights the significance of cooperation between higher education institutions and schools in ensuring the effectiveness of pedagogical practice.